Konsep Teologi Dalam Cerita Srinandi - Putri, Ni Kadek Ayu Kristini (Satya Widya: Jurnal Studi Agama, 2022)
Literature created in antiquity has various themes about human life. The stories of life that do not escape writing in the form of prose, papyrus and speech in the form of lontar are very identical to life today. The story of Srinandi in the form of spoken literature is not far from today's life, like a modern soap opera with a different era. To produce valid and reliable data, this research uses qualitative research methods. To produce logical data, this article performs several stages of data sorting in the form of: 1). Reducing data, 2). Display data, 3). Verify data and, 4). Interpret article data. Related references really support the validity of a scientific work, therefore library techniques are also used through literature exploration on Google Scholar. The story in the lontar Srinandi which tells the story of a marriage that ends in murder with a third person element is very thick with the intervention of God himself. It was his devotion to Srinandi himself that resulted in the form of heaven, because of Srinandi's life journey who was very obedient and devoted during his life.